Online Calculators

# Present Value Calculator

Present Value Calculator
Interest

Cash Flow: annuity, optional

Present Value (PV) of the Lump Sum

\$ 8,883.50

## Calculator Use

Find the present value of a future sum of money. The present value calculator answers the question, "What do I need to invest today to have a specific sum of money at a future date?"

You can think of present value as the amount you need to save now to have a certain amount of money in the future. The present value formula applies a discount to your future value amount, deducting interest earned to find the present value in today's money.

## Present Value Formula and Calculator

The present value formula is PV=FV/(1+i)n, where you divide the future value FV by a factor of 1 + i for each period between present and future dates.

Input these numbers in the present value calculator for the PV calculation:

• The future value sum FV
• Number of time periods (years) t, which is n in the formula
• Interest rate R, which is i in the formula
• Compounding frequency
• Cash flow payments going out
• Annuity growth rate

The present value of an amount of money is worth more in the future when it is invested and earns interest.

The present value is the amount you would need to invest now, at a known interest and compounding rate, so that you have a specific amount of money at a specific point in the future.

You can enter 0 for any variable you'd like to exclude when using this calculator. Our other present value calculators offer more specialized present value calculations.

## What's in the Present Value Calculation

The present value calculator uses the following to find the present value PV of a future sum plus interest, minus cash flow payments:

Future Value FV
Future value of a sum of money
Number of time periods t
• Time periods is typically a number of years
• Be sure all your inputs use the same time period unit (years, months, etc.)
• Enter p or perpetuity for a perpetual annuity
Interest Rate R
The nominal interest rate or stated rate, as a percentage
Compounding m
• The number of times compounding occurs per period
• Enter 1 for annual compounding which is once per year
• Enter 4 for quarterly compounding
• Enter 12 for monthly compounding
• Enter 365 for daily compounding
• Enter c or continuous for continuous compounding
Cash flow annuity payments going out PMT
The payment amount each period
Growth rate G
The growth rate of annuity payments per period entered as a percentage
Number of payments q per period
• Payment frequency
• Enter 1 for annual payments which is once per year
• Enter 4 for quarterly payments
• Enter 12 for monthly payments
• Enter 365 for daily payments
When do annuity payments occur T
• Select end which is an ordinary annuity for payments at the end of the period
• Select beginning for payments at the beginning of the period
Present Value PV
The result of the PV calculation is the present value of any future value sum plus future cash flows or annuity payments

The sections below show how to derive present value formulas. For a list of the formulas presented here see our Present Value Formulas page.

## Present Value Formula Derivation

The future value (FV) of a present value (PV) sum that accumulates interest at rate i over a single period of time is the present value plus the interest earned on that sum. The mathematical equation is

$$FV=PV+PVi$$

or

$$FV=PV(1+i)$$

For each period into the future the accumulated value increases by an additional factor (1 + i). Therefore, the future value accumulated over, say 3 periods, is given by

$$FV_{3}=PV_{3}(1+i)(1+i)(1+i)=PV_{3}(1+i)^{3}$$

or generally

$$FV_{n}=PV_{n}(1+i)^{n}$$
Equation 1a

Likewise we can solve for PV to get

$$PV_{n}=\dfrac{FV_{n}}{(1+i)^n}$$
Equation 1b

The equations we have are (1a) the future value of a present sum and (1b) the present value of a future sum at a periodic interest rate i where n is the number of periods in the future. Commonly this equation is applied with periods as years but it is less restrictive to think in the broader terms of periods. Dropping the subscripts from (1b) we have:

### Present Value of a Future Sum

$$PV=\dfrac{FV}{(1+i)^n}$$
Equation 1

## Present Value of an Annuity Formula Derivation

An annuity is a sum of money paid periodically, (at regular intervals). Let's assume we have a series of equal present values that we will call payments (PMT) for n periods at a constant interest rate i.  We can calculate FV of the series of payments 1 through n using formula (1) to add up the individual future values.

$$PV=\dfrac{PMT}{(1+i)^1}+\dfrac{PMT}{(1+i)^2}+\dfrac{PMT}{(1+i)^3}+...+\dfrac{PMT}{(1+i)^n}$$
Equation 2a

multiply both sides of this equation by (1 + i) to get

$$PV(1+i)=PMT+\dfrac{PMT}{(1+i)^1}+\dfrac{PMT}{(1+i)^2}+\dfrac{PMT}{(1+i)^3}+...+\dfrac{PMT}{(1+i)^{n-1}}$$
Equation 2b

subtracting the equation for PV (2a) from the equation for PV(1 + i) (2b) most terms cancel and we are left with

$$PV(1+i)-PV=PMT-\dfrac{PMT}{(1+i)^n}$$

pulling out like terms on both sides

$$PV((1+i)-1)=PMT\left[1-\dfrac{1}{(1+i)^n}\right]$$

cancelling 1's on the left

$$PVi=PMT\left[1-\dfrac{1}{(1+i)^n}\right]$$

and finally, after dividing through by i, the present value of an ordinary annuity, payments made at the end of each period, is

$$PV=\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right]$$
Equation 2c

For an annuity due, payments made at the beginning of each period instead of the end, therefore payments are now 1 period closer to the PV.  We need to discount each future value payment in the formula by 1 period. This could be written on (1b) as

$$PV_{n}=\dfrac{FV_{n}}{(1+i)^{n-1}}$$

but factoring out the (1 + i)

$$PV_{n}=\dfrac{FV_{n}}{(1+i)^{n}}(1+i)$$

So, multiplying each payment in equation (2a), or the right side of equation (2c), by the factor (1 + i) will give us the equation of PV for an annuity due.  This can be written more generally as

### Present Value of an Annuity

$$PV=\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right](1+iT)$$
Equation 2

where T represents the type. (similar to Excel formulas) If payments are at the end of the period it is an ordinary annuity and we set T = 0.  If payments are at the beginning of the period it is an annuity due an we set T = 1.

### Present Value of an Ordinary Annuity

if T = 0, payments are at the end of each period and we have the formula for present value of an ordinary annuity

$$PV=\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right]$$
Equation 2.1

### Present Value of an Annuity Due

if T = 1, payments are at the beginning of each period and we have the formula for present value of an annuity due

$$PV=\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right](1+i)$$
Equation 2.2

## Present Value Growing Annuity Formula Derivation

In a growing annuity, each payment, after the first, is increased by a factor g such that payment 2 is PMT(1 + g), payment 3 is PMT(1 + g)(1 + g), payment 4 is PMT(1 + g)(1 + g)(1 + g), etc.  Modifying equation (2a) to include growth we get

$$PV=\dfrac{PMT}{(1+i)^1}+\dfrac{PMT(1+g)^1}{(1+i)^2}+\dfrac{PMT(1+g)^2}{(1+i)^3}+\dfrac{PMT(1+g)^3}{(1+i)^4}+...+\dfrac{PMT(1+g)^{n-1}}{(1+i)^n}$$
Equation 3a

Multiply PV by (1+i)/(1+g) to get

$$PV\dfrac{(1+i)}{(1+g)}=\dfrac{PMT}{(1+g)^1}+\dfrac{PMT}{(1+i)^1}+\dfrac{PMT(1+g)^1}{(1+i)^2}+\dfrac{PMT(1+g)^2}{(1+i)^3}+...+\dfrac{PMT(1+g)^{n-2}}{(1+i)^{n-1}}$$
Equation 3b

subtracting equation (3a) from (3b) most terms cancel and we are left with

$$PV\dfrac{(1+i)}{(1+g)}-PV=\dfrac{PMT}{(1+g)}-\dfrac{PMT(1+g)^{n-1}}{(1+i)^{n}}$$

with some algebraic manipulation, multiplying both sides by (1 + g) we have

$$PV(1+i)-PV(1+g)=PMT-\dfrac{PMT(1+g)^{n}}{(1+i)^{n}}$$

pulling like terms out on both sides

$$PV(1+i-1-g)=PMT\left[1-\left(\dfrac{1+g}{1+i}\right)^n\right]$$

cancelling the 1's on the left then dividing through by (i-g) we finally get

### Present Value of a Growing Annuity (g ≠ i)

$$PV=\dfrac{PMT}{(i-g)}\left[1-\left(\dfrac{1+g}{1+i}\right)^n\right]$$

Similar to equation (2), to account for whether we have a growing annuity due or growing ordinary annuity we multiply by the factor (1 + iT)

$$PV=\dfrac{PMT}{(i-g)}\left[1-\left(\dfrac{1+g}{1+i}\right)^n\right](1+iT)$$
Equation 3

### Present Value of a Growing Annuity (g = i)

If g = i you'll notice that (1 + g) terms cancel in equation (3a) and we get

$$PV=\dfrac{PMT}{(1+i)}+\dfrac{PMT}{(1+i)}+\dfrac{PMT}{(1+i)}+...+\dfrac{PMT}{(1+i)}$$

since we now have n instances of PMT/(1+i) we can reduce the equation. Also accounting for an annuity due or ordinary annuity, multiply by (1 + iT), and we get

$$PV=\dfrac{PMTn}{(1+i)}(1+iT)$$
Equation 4

### Present Value of a Perpetuity (t → ∞ and n = mt → ∞)

For a perpetuity, perpetual annuity, time and the number of periods goes to infinity therefore n goes to infinity.  As n increases the 1/(1 + i)n term in formula (2) goes to 0 leaving

$$PV=\dfrac{PMT}{i}(1+iT)$$
Equation 5

### Present Value of a Growing Perpetuity (g < i) (t → ∞ and n = mt → ∞)

Likewise for a growing perpetuity, where we must have g<i, since (1 + i)n grows faster than (1 + g)n, that term goes to 0 in formula (3) and it reduces to

$$PV=\dfrac{PMT}{(i-g)}(1+iT)$$
Equation 6

### Present Value of a Growing Perpetuity (g = i) (t → ∞ and n = mt → ∞)

Since n also goes to infinity (n → ∞) as t goes to infinity (t → ∞), we see that Present Value with Growing Annuity (g = i) also goes to infinity

$$PV=\dfrac{PMTn}{(1+i)}(1+iT)\rightarrow\infty$$
Equation 7

## Present Value Formula for Combined Future Value Sum and Cash Flow (Annuity):

We can combine equations (1) and (2) to have a present value equation that includes both a future value lump sum and an annuity. This equation is comparable to the underlying time value of money equations in Excel.

### Present Value

$$PV=\dfrac{FV}{(1+i)^n}+\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right](1+iT)$$
Equation 8

As in formula (2.1) if T = 0, payments at the end of each period, we have the formula for present value with an ordinary annuity

$$PV=\dfrac{FV}{(1+i)^n}+\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right]$$
Equation 8.1

As in formula (2.2) if T = 1, payments at the beginning of each period, we have the formula for present value with an annuity due

$$PV=\dfrac{FV}{(1+i)^n}+\dfrac{PMT}{i}\left[1-\dfrac{1}{(1+i)^n}\right](1+i)$$
Equation 8.2

#### Present Value when i = 0

In the case where i = 0 and we look back at equations (1) and (2a) to see that the combined present value formula can reduce to

$$PV=FV+PMTn(1+iT)$$

### Present Value with Growing Annuity (g ≠ i)

rewritten from formula (3)

$$PV=\dfrac{FV}{(1+i)^n}+\dfrac{PMT}{(i-g)}\left[1-\left(\dfrac{1+g}{1+i}\right)^n\right](1+iT)$$
Equation 9

### Present Value with Growing Annuity (g = i)

rewritten from formula (4)

$$PV=\dfrac{FV}{(1+i)^n}+\dfrac{PMTn}{(1+i)}(1+iT)$$
Equation 10

Note on Compounding m, Time t, and Rate r

Formula (8) can be expanded to account for compounding (m).

$$PV=\dfrac{FV}{(1+\frac{r}{m})^{mt}}+\dfrac{PMT}{\frac{r}{m}}\left[1-\dfrac{1}{(1+\frac{r}{m})^{mt}}\right](1+(\frac{r}{m})T)$$
Equation 11

where n = mt and $$i = \frac{r}{m}$$.  t is the number of periods, m is the compounding intervals per period and r is rate per period t. (this is easily understood when applied with t in years, r the nominal rate per year and m the compounding intervals per year) When written in terms of i and n, i is the rate per compounding interval and n is the total compounding intervals although this can still be stated as "i is the rate per period and n is the number of periods" where period = compounding interval. "Period" can be a broad term.

Related to the calculator inputs, r = R/100 and g = G/100. If compounding (m) and payment frequencies (q) do not coincide in these calculations, r is converted to an equivalent rate to coincide with payments then n and i are recalculated in terms of payment frequency, q. The first part of the equation is the present value of the future sum and the second part is the present value of an annuity.

### Present Value of a Perpetuity (t → ∞ and n = mt → ∞)

For a perpetuity, perpetual annuity, the number of periods t goes to infinity therefore n goes to infinity.  The FV term in equation (11) goes to 0 and the 1/(1 + i)n in the second term also goes to 0 leaving just formula (5)

$$PV=\dfrac{PMT}{i}(1+iT)$$
Equation 5

### Present Value of a Growing Perpetuity (g < i) (t → ∞ and n = mt → ∞)

Likewise for a growing perpetuity, where we must have g<i, since (1 + i)n grows faster than (1 + g)n, this term in formula (9) reduces to formula (6)

$$PV=\dfrac{PMT}{(i-g)}(1+iT)$$
Equation 6

### Present Value of a Growing Perpetuity (g = i) (t → ∞ and n = mt → ∞)

Since n also goes to infinity (n → ∞) as t goes to infinity (t → ∞), we see that Present Value with Growing Annuity (g = i) (10) goes to infinity and we are back at equation (7)

$$PV=\dfrac{PMTn}{(1+i)}(1+iT)\rightarrow\infty$$
Equation 7

## Continuous Compounding (m → ∞)

We look back to formula (11) for present value where m is the compounding per period t, t is the number of periods and r is the compounded rate with $$i = \frac{r}{m}$$ and n = mt.

$$PV=\dfrac{FV}{(1+\frac{r}{m})^{mt}}+\dfrac{PMT}{\frac{r}{m}}\left[1-\dfrac{1}{(1+\frac{r}{m})^{mt}}\right](1+(\frac{r}{m})T)$$
Equation 11

The effective rate is ieff = ( 1 + ( r / m ) )m - 1 for a rate r compounded m times per period.  It can be proven mathematically that as m → ∞, ieff (the effective rate of r with continuous compounding) reaches the upper limit equal to er - 1.

### Present Value with Continuous Compounding (m → ∞)

Removing the m and changing r to the effective rate of r, er - 1, in formula (11), formulas (8) & (11) for Present Value become

$$PV=\dfrac{FV}{(1+e^{r}-1)^{t}}+\dfrac{PMT}{e^{r}-1}\left[1-\dfrac{1}{(1+e^{r}-1)^{t}}\right](1+(e^{r}-1)T)$$

cancelling out 1's where possible we get the final formula for present value with continuous compounding

$$PV=\dfrac{FV}{e^{rt}}+\dfrac{PMT}{(e^r-1)}\left[1-\dfrac{1}{e^{rt}}\right](1+(e^r-1)T)$$
Equation 12

for an ordinary annuity

$$PV=\dfrac{FV}{e^{rt}}+\dfrac{PMT}{(e^r-1)}\left[1-\dfrac{1}{e^{rt}}\right]$$
Equation 12.1

for an annuity due

$$PV=\dfrac{FV}{e^{rt}}+\dfrac{PMT}{(e^r-1)}\left[1-\dfrac{1}{e^{rt}}\right]e^r$$
Equation 12.2

### Present Value of a Growing Annuity (g ≠ i) and Continuous Compounding (m → ∞)

We can modify equation (3a) for continuous compounding, replacing i's with er - 1 and we get:

$$PV=\dfrac{PMT}{(1+e^{r}-1)^1}+\dfrac{PMT(1+g)^1}{(1+e^{r}-1)^2}+\dfrac{PMT(1+g)^2}{(1+e^{r}-1)^3}+\dfrac{PMT(1+g)^3}{(1+e^{r}-1)^4}+...+\dfrac{PMT(1+g)^{n-1}}{(1+e^{r}-1)^n}$$

which reduces to

$$PV=\dfrac{PMT}{e^{1r}}+\dfrac{PMT(1+g)^1}{e^{2r}}+\dfrac{PMT(1+g)^2}{e^{3r}}+\dfrac{PMT(1+g)^3}{e^{4r}}+...+\dfrac{PMT(1+g)^{n-1}}{e^{nr}}$$
Equation 13a

Multiplying (13a) by er/(1+g)

$$\dfrac{PVe^{1r}}{(1+g)}=\dfrac{PMT}{(1+g)}+\dfrac{PMT}{e^{1r}}+\dfrac{PMT(1+g)^1}{e^{2r}}+\dfrac{PMT(1+g)^2}{e^{3r}}+...+\dfrac{PMT(1+g)^{n-2}}{e^{(n-1)r}}$$
Equation 13b

subtracting (13a) from (13b) most terms cancel out leaving

$$\dfrac{PVe^{1r}}{(1+g)}-PV=\dfrac{PMT}{(1+g)}-\dfrac{PMT(1+g)^{n-1}}{e^{nr}}$$

multiplying through by (1+g)

$$PVe^{r}-PV(1+g)=PMT-\dfrac{PMT(1+g)^{n}}{e^{nr}}$$

solving this equation for PV and adding on the term to account for whether we have a growing annuity due or growing ordinary annuity we multiply by the factor (1 + (er-1)T)

$$PV=\dfrac{PMT}{e^{r}-(1+g)}\left[1-\dfrac{(1+g)^{n}}{e^{nr}}\right](1+(e^{r}-1)T)$$
Equation 13

### Present Value of a Growing Annuity (g = i) and Continuous Compounding (m → ∞)

Starting with equation (4) replacing i's with er - 1 and simplifying we get:

$$PV=\dfrac{PMTn}{e^{r}}(1+(e^r-1)T)$$
Equation 14

### Present Value of a Perpetuity (t → ∞) and Continuous Compounding (m → ∞)

As t → ∞, ert → ∞ and formula (12) becomes

$$PV=\dfrac{PMT}{(e^r-1)}(1+(e^r-1)T)$$
Equation 15

### Present Value of a Growing Perpetuity (g < i) (t → ∞) and Continuous Compounding (m → ∞)

As t → ∞, n → ∞ and enr in formula (13) grows fastest causing this term to go to 0 and we are left with:

$$PV=\dfrac{PMT}{e^{r}-(1+g)}(1+(e^{r}-1)T)$$
Equation 16

### Present Value of a Growing Perpetuity (g = i) (t → ∞) and Continuous Compounding (m → ∞)

From our equation for Present Value of a Growing Perpetuity (g = i) (7) replacing i with er-1 we end up with the following formula but since n → ∞ for a perpetuity this will also always go to infinity.

$$PV=\dfrac{PMTn}{e^{r}}(1+(e^r-1)T)\rightarrow\infty$$
Equation 17

Cite this content, page or calculator as:

Furey, Edward "Present Value Calculator" at https://www.calculatorsoup.com/calculators/financial/present-value-calculator.php from CalculatorSoup, https://www.calculatorsoup.com - Online Calculators

Last updated: March 26, 2024